PENGARUH FABRIKASI BERUPA PERBANDINGAN PRODUK OBAT PATEN PANADOL DAN SANMOL - Rahmawati, Shinta; Aryzki, Saftia (Jurnal Farmasi & Sains Indonesia, 2024)
Availability is a measure of the rate and amount of a therapeutically active drug that reaches the general circulation. As for bioequivalence requirements, a requirement made by the Food and Drug Administration (FDA) for in vitro and/or in vivo testing of certain medicinal products, these requirements must be met as a condition for marketing. Bioequivalence of a medicinal product is pharmaceutical equivalent or an alternative is a preparation whose rate and amount of absorption do not differ significantly when given at the same dose and experimental conditions. Several drugs that have the same amount of absorption but differ in absorption rate can be considered pharmaceutical equivalent if the difference in absorption rate does not cause a significant difference in clinical effects.